The Free Rider Problem and a Social Custom Model of Trade Union Membership - Booth, Alison L. (Quarterly Journal of Economics, 1985)
Journal Article The Free Rider Problem and a Social Custom Model of Trade Union Membership Get access Alison L. Booth Alison L. Booth The City University, London Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 100, Issue 1, February 1985, Pages 253–261, https://doi.org/10.2307/1885744 Published: 01 February 1985